Graphic Novel Adaptation as a Subgenre (Franco- and Anglophone Texts) - M. G. Merkulova; I. G. Prudius (Научный диалог, 2024)
The objective of this study is to define the graphic novel adaptation as a distinct subgenre of the graphic novel and to develop a cohesive methodology for its examination. The research material comprises Franco- and Anglophone graphic novel adaptations published since the early 2000s. It is noted that this subgenre has become one of the most popular forms of mass literature, characteristic of the twenty-first century as an era of visual culture. Based on a review of theoretical studies, the fundamental characteristics of graphic novel adaptations are articulated. An analysis of works from the past decade demonstrates the evolution of the subgenre under consideration. Specifically, it is observed that (1) the original narrative line is modified through the incorporation of themes and issues relevant to twenty-first-century individuals; (2) there is an increased complexity in character development, structure, and chronotope; (3) a philosophical dimension is foregrounded. It is shown that graphic novel adaptations can be categorized into two types based on target audience: mass (“low brow”) and intellectual (“high brow”). The “low brow” type primarily aims to popularize the reading of classic texts, while the “high brow” type represents an authorial interpretation of a well-known literary work. The intellectual form (“high brow”) has become increasingly prevalent since the 2010s.